CRKL promotes lung cancer cell invasion through ERK‐MMP9 pathway. Issue 1 (24th March 2014) - Lin, Fu; Chengyao, Xie; Qingchang, Li; Qianze, Dong; Enhua, Wang; Yan, Wang; Schabath, Matthew B.; DiGiovanni, John
<x xml:space="preserve">Abstract</x> CRKL is recently defined as a new oncogene, which plays a role in the lung cancer progression. However, the potential mechanism of CRKL in human non‐small cell lung cancer cell invasion is obscure. We investigated the potential mechanism of CRKL in lung cancer cell invasion using immunohistochemistry, plasmid transfection, Western blotting, real‐time PCR, matrigel invasion assay, chromatin immunoprecipitation assay, and luciferase reporter assay. CRKL expression is higher in lymph node metastatic tumor compared with primary tumor. CRKL overexpression enhanced cell invasion and MMP9 expression in both HBE and H1299 cell lines. There was a significant correlation between CRKL overexpression and high MMP9 expression in primary tumors. MMP‐9 antibody treatment significantly blocked cell invasion. CRKL overexpression also activated AP‐1 luciferase reporter activity, ERK phosphorylation and association of c‐fos to MMP9 promoter. Treatment with ERK inhibitor PD98059 in cells with CRKL transfection inhibited ERK activity, cell invasion, and MMP9 expression. These results suggested that overexpression of CRKL promoted cell invasion through upregulation of MMP9 expression and activation of ERK pathway. © 2014 Wiley Periodicals, Inc.